Pembuatan Filter Air Sungai dan Penyediaan Penampungan Air Bersih di Desa Penadaran - Adelia Puspitasari; Agnes Oktavi Maharani; Ratih Pramitasari; Syahiful Yudhi Nugroho; Wahyuni Ainuly Umayah; Kania Salma Nur Prastiwi; Agil Fahrudi Hibatulla; Rani Hardiningtyas; Deyani Deyani; Alif Maulana Iqbal (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Penadaran Village is a village in Gubug District, Grobogan Regency, Central Java Province. The dry season makes residents in Penadaran Village experience problems with clean water sources. The purpose of community service is to make filters and provide clean water reservoirs for the residents of Penadaran Village. The implementation methods used are: (1) Conducting Tuntang River Water Quality Test, (2) Designing a scheme for clean water filters and reservoirs, (3) Making clean water filters and reservoirs. The location is in Kedungkakap Hamlet, Penadaran Village. The implementation time is August – October 2021. The results of the implementation of community service, obtained the results of the Tuntang River Water Quality Test, namely, Iron: 0.496 mg/L, COD: 301 mg/L, Chloride: 7.30 mg/L, manganese: 0.502 mg/ L, the river water filter scheme uses a system with 3 settling tanks and 2 mixed bed tubes. The shelter uses a 3300 ml Toren with a tower as high as 3 m from the ground. There are 17 families who have received clean water supply from the new source